2022
DOI: 10.1038/s41598-022-12954-3
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Analysis of Prognostic and immune infiltrates for FOXPs Transcription Factors in Human Breast Cancer

Abstract: Forkhead-box-P family include FOXP1/2/3/4 and its clinical significance still remains unclear in breast cancer (BRCA). We analysed the expressions of FOXPs in BRCA patients to determine diagnostic and prognostic values. Our results indicated that the transcriptional levels of FOXP3/4 were up-regulated in BRCA patients, but FOXP2 were down-regulated. No statistically significant correlation were found between the expression levels of FOXPs in Pathologic stage. FOXP2/3 had a significantly high AUC value in the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 56 publications
0
10
1
Order By: Relevance
“…NAT10/ac4C/FOXP1 axis was reported to facilitate immunosuppression and overexpression of FOXP1 was found to be positively related to the infiltration of activated CD4+ T cells and Tregs in cervical cancer, 33 which supports our hypothesis. In breast cancer, the expression of FOXP1 is positively correlated with the infiltration of CD4 + T cells, CD8 + T cells, neutrophils and macrophages, but different from our findings, the expression of FOXP1 is negatively correlated with B cells 52 . We speculated that FOXP1 may regulate different immune infiltrating cells depending on different tumours.…”
Section: Discussioncontrasting
confidence: 99%
“…NAT10/ac4C/FOXP1 axis was reported to facilitate immunosuppression and overexpression of FOXP1 was found to be positively related to the infiltration of activated CD4+ T cells and Tregs in cervical cancer, 33 which supports our hypothesis. In breast cancer, the expression of FOXP1 is positively correlated with the infiltration of CD4 + T cells, CD8 + T cells, neutrophils and macrophages, but different from our findings, the expression of FOXP1 is negatively correlated with B cells 52 . We speculated that FOXP1 may regulate different immune infiltrating cells depending on different tumours.…”
Section: Discussioncontrasting
confidence: 99%
“…But the prognostic value of FOXP3 in cancer appears to be divergent. As a transcription factor, FOXP3 may play a regulatory role by directly binding to specific tumor-related genes in BC (9). This ability of transcriptional regulation may well be the potential superiority of FOXP3 in relative to prior biomarkers of BC.…”
Section: Introductionmentioning
confidence: 99%
“…4 The previous studies have showed that FOXPs and GPI were prognostic biomarkers for breast cancer. 5,6 However, these biomarkers were not suitable for all breast cancer patients, owing to tumor heterogeneity and individual differences. 7 Therefore, to improve patient survival, identifying additional suitable prognostic biomarkers is essential to enhance the precision of clinical outcome predictions, tailor personalized treatment strategies more effectively, and innovate new therapeutic approaches for breast cancer.…”
Section: Introductionmentioning
confidence: 99%